Leveraging whole blood based functional flow cytometry assays to open new perspectives for rheumatoid arthritis translational research - Celia Cartagena García; Nathalie Balandraud; Jean Roudier; Pierre Lafforgue; Nathalie Lambert; Jean-Marc Busnel (Scientific Reports, 2022)
Abstract Despite introduction of biological disease modifying anti-rheumatic drugs (DMARDs) for Rheumatoid arthritis (RA) treatment, therapeutic strategies do not always lead to disease control and remission. Hence, a more efficient patient stratification and monitoring biomarkers and tools are needed to enable a more personalized medicine. We used a whole blood based functional flow cytometry assay to characterize immune cells from RA patients (treated or not), healthy donors and psoriatic arthritis (PsA) patients according to their responses to LPS and/or anti-TNFα (infliximab, IFX). Activation marker expression was measured using a 10-color flow cytometry panel following a no-wash protocol. Naïve-to-treatment RA patients had a stronger inflammatory profile in comparison to healthy donors at basal level. Higher expression of activation markers (CD69 and/or CD11b) on NK, B cells and granulocytes and lower expression of the adhesion molecule CD62L were measured on monocytes, granulocytes and B cells. After LPS, naïve RA patients’ cells were less capable of regulating CD69, CD11b, CD16 or CD62L showing impaired activation capabilities. Upon LPS and IFX co-incubation, hierarchical clustering analysis showed different profiles between cohorts. We believe that this whole blood-based approach should further be assessed for RA patient characterization as it provides new perspectives for stratification and/or monitoring.